PENGARUH LINGKUNGAN KERJA DAN PENEMPATAN KARYAWAN TERHADAP MOTIVASI KERJA KARYAWAN PADA PT. BANK RIAU KEPRI CABANG DUMAI - Muhammad Halimi; Jumiati Sasmita; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted on employees of PT. Bank Riaukepri Dumai branch office. The aim of this study is to analyzing the influence of the working environment variables and employees placement to working motivation on production department at PT. Bank Riaukepri Dumai branch office. Sampling was done by taking the overall population as respondents as many as 39 people. The analytical method used was descriptive of quantitative methods, data analysis done partially and simultaneously (multiple linear regression analysis with SPSS version 17.0). From the results of simultaneous testing (the F test), shows that all the independent variables studied had a significant impact on employee motivation variable. Partial regression test (the T test) shows that the employees placement variables reveal more significant effect on employee motivation at PT Bank Riaukepri Dumai Branch Office. The magnitude of the effect caused by these two variables together against the dependent variable was 66.1%, it means that the variable motivation and work environment jointly influence employee performance variable with the percentage of 66.1% while 33.9%, affected by other factors that did not participate in this study. From the research can be concluded that the work environment and employee placement and simultaneous partial reveal positive and significant impact on employee motivation at production department PT. Bank Riaukepri Dumai branch office. In addition, the variable of employees placement is more significantly effect on the motivation of employees, when compared with the working environment variable.Keywords : working environment, employees placement and working motivation